Reflection of Moral Integrity in the Novel Al-Hubb Fii Zaman An-Nafth by Nawal El-Saadawi (A Sociological Literature Study) - Siti Khofifah; Maman Abdul Djaliel; Yadi Mardiansyah (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
Discrimination against women in the workplace is still a complex social problem, including in the field of archaeology. NovelAl-Hubb Fii Zaman An-Nafth depicts the story of a female archaeologist who experiences gender discrimination in her work. The main character is prohibited from going looking for statues without permission, while her male colleagues do not face similar restrictions. This study aims to describe the sociological review of literature on moral integrity in the novel. This study uses a qualitative descriptive method by analyzing the patriarchal and moral areas presented in the novel. The results show that the female character in these novel fights discrimination due to the patriarchal culture inherent in society through self-motivation and internal drive. She shows courage and moral firmness in facing the injustice she experiences. In addition, the moral integrity of the main character is reflected in honesty, consistency, commitment, perseverance, and self-discipline. Values such as responsibility, trust, and justice are also principles that are firmly held in her struggle. This study reveals that moral integrity plays an important role in dealing with gender discrimination. The female character in this novel represents an empowered woman, who not only opposes injustice but also proves that morality, perseverance, and courage can be the main weapons in fighting discrimination. These findings provide new perspectives on how literature can reflect social realities and promote gender equality in society.